Hypertension and atrial fibrillation in obstructive sleep apnea: Is it a menopause issue?. (June 2019) - Perger, Elisa; Pengo, Martino F.; Lombardi, Carolina
Highlights: Obstructive sleep apnea is a common disease associated with increased cardiovascular risk. Cardiovascular consequences of OSA are chronic systemic arterial hypertension and arrhythmias, in particular atrial fibrillation. The prevalence of obstructive sleep apnea is affected by age and gender This review has been focussed on the potential role of menopause status in determining women's cardiovascular risk profile. Abstract: Obstructive sleep apnoea (OSA) is a common disorder, in which loss of pharyngeal dilator muscle tone during sleep causes recurrent collapse of the upper airway and temporary cessation of breathing. Repeated apneas and hypopneas lead to cycles of intermittent hypoxia/hypercapnia, increased negative intrathoracic pressure and arousals from sleep. These consequences of OSA are associated with a cascade of cardiovascular and neurohumoral consequences, including sympathetic nervous system hyperactivity, raised heart rate variability, increases in blood pressure, myocardial wall stress, oxidative stress, systemic inflammation, platelet aggregation and impaired vascular endothelial function, which contribute, in turn, to increased cardiovascular risk and, in particular, to the development of chronic systemic arterial hypertension and arrhythmias, especially atrial fibrillation (AF). Given that the prevalence of OSA is modified by age and gender, OSA-related cardiovascular diseases may also be affected by the same factors. This review focuses on the potential role of OSA in systemic arterial hypertension and AF, and discusses the most interesting studies on age and gender as predisposing factors.